Nuclear circRNA: Impairing genome stability via circR loops - Jiao Jiao; Zhijun Zhang (Wiley, 2023)
Abstract Conn et al. have recently reported circRNA: DNA hybrids (circR loops) to promote oncogenic gene translocations and impair genome stability which drive leukemia. Herein, we will summarize potential molecular mechanisms and discuss clinical significance of uncovering circR loops as endogenous RNA carcinogens.